2022
DOI: 10.1145/3555531
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and the Quantified Workplace: Tensions around Personal Sensing Interventions for Stress in Resident Physicians

Abstract: Recent research has explored computational tools to manage workplace stress via personal sensing, a measurement paradigm in which behavioral data streams are collected from technologies including smartphones, wearables, and personal computers. As these tools develop, they invite inquiry into how they can be appropriately implemented towards improving workers' well-being. In this study, we explored this proposition through formative interviews followed by a design provocation centered around measuring burnout i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…Although our results do not contest the objectivity of using digitally tracked data to measure behavior, they do question the objectivity of these data with respect to measuring a patient’s mental health. Researchers in human-computer interaction have echoed this point that digital measures may reduce mental health to biobehavioral data points, missing more interpretive aspects of mental health that cannot be easily quantified using passive tracking [ 20 , 33 ]. These critiques may also apply to specific forms of active PGHD, for example, behavioral data collected during health-related active tasks, although participants did not discuss these forms of active data during the interviews.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although our results do not contest the objectivity of using digitally tracked data to measure behavior, they do question the objectivity of these data with respect to measuring a patient’s mental health. Researchers in human-computer interaction have echoed this point that digital measures may reduce mental health to biobehavioral data points, missing more interpretive aspects of mental health that cannot be easily quantified using passive tracking [ 20 , 33 ]. These critiques may also apply to specific forms of active PGHD, for example, behavioral data collected during health-related active tasks, although participants did not discuss these forms of active data during the interviews.…”
Section: Discussionmentioning
confidence: 99%
“…We created an interview guide composed of 3 sections following the speculative design tradition [ 31 , 33 ]. The interview opened with an introductory section to learn about the participants’ clinical practice.…”
Section: Methodsmentioning
confidence: 99%
“…There has been increasing research in the CSCW space where group modeling techniques are applied to gather behavioral data streams of individuals and their groups on topics related to health, engagement, and performance. Alder et al 's study on how passive personal sensing technologies could help resident physicians with their burnout symptoms revealed the potential for tracking a resident's work deviations from their cohort's norm [1]. Separately, Zakaria et al reported a significant predictor of stress is the deviations between the student and their group's norm, distinguishing casual groups from workgroups [75] and their social identification to respective groups [76].…”
Section: Supporting Group Modeling Applicationsmentioning
confidence: 99%
“…Consider our case study of analyzing longitudinal behavioral change among students on campus in Section 6.2 to separately analyze the behaviors of resident physicians in their workplaces [1] as an example. Such a system would require individual stakeholders to trust the institution enormously.…”
Section: Application Of Ethicsmentioning
confidence: 99%
See 1 more Smart Citation